Evaluasi Kebijakan Fiskal Dan Moneter Dalam Mendukung Pertumbuhan Ekonomi Berkelanjutan Di Indonesia - Mochamad Salva Putra E; Agus Wahyudi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Abstract, Fiscal and monetary policies have an important role in sustainable economic growth in Indonesia. This research aims to evaluate the effectiveness of fiscal and monetary policies in achieving sustainable economic growth. The research method applied is descriptive analysis using secondary data obtained from various trusted sources. The research results show that fiscal policy, which includes budget regulation, taxes and subsidies, has made a positive contribution to economic growth. However, efforts are still needed to improve the efficiency of budget management and transparency in the use of public funds. Meanwhile, monetary policy, which includes setting interest rates and the money supply, also has a significant impact on economic growth. However, the need to balance price stability and economic growth remains a challenge. In conclusion, to achieve sustainable economic growth, close coordination between fiscal and monetary policies is needed. In addition, comprehensive structural reforms and increasing institutional capacity are very important to create a supportive environment to ensure sustainable economic growth in Indonesia.